Strategi Pemberdayaan Ekonomi Kreatif di Kampung Kue Surabaya Sebagai Upaya Pemulihan Ekonomi Masyarakat di Masa Pandemi - Ayundha Evanthi; Daisy Marthina Rosyanti; Ratih Mukti Azhar; Ilham Hardi; , Gerry Hutomo Orlando (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Covid-19 has significantly shaken the wheels of the economy of people in all countries including Indonesia. MSMEs, which are one of the important pillars in the Indonesian economy, are also affected by these conditions. The main problem faced by MSMEs during the pandemic is sluggish market demand and high operating costs the market. Kampung Kue is one of the MSMEs that was formed organically through the initiative of residents who were also affected during the pandemic. Since the pandemic occurred, Kampung Kue has experienced a decline in turnover, lost some market share and some of them were forced to temporarily close their businesses. Not only that, there is still a lack of brand awareness and weak readiness to go digital, as well as the cooperation of the entire MSME community in Kampung Kue also still requires special attention for the growth of Kampung Kue. The purpose of this activity is to provide knowledge and empowerment of Kampung Kue business actors. The results of the activity, besides increasing knowledge, it is hoped that the problems faced can be solved and find appropriate strategies so that they can encourage the growth of the creative economy of the people who are members of Kampung Kue